Decontamination By Personel of NBC Company of Indonesian Arny at Wisma Atlet- Emergency Hospital for Covid-19: Work Load, Stress Work, and Personnel Performance - Tri Ambodo; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2023)
Purpose of this writing is to discuss the relationship of work load, stress work, and military personnel performance of Kizi Nubika Pusziad (Indonesian Army Engineers-Nuclear-Biological-Chemical Company) including their supporting proofs when conducting his decontamination task at Wisma Atlet RSDC (Wisma Atlet- Emergency Hospital for Covid-19) in Kemayoran – Jakarta as part of military operation other than war in responding to Covid-19 spread launched by TNI (Indonesia National Armed Forces) in the middle of year 2020, at the beginning of Covid-19 Pandemic, and in the period of anxiety and panic among Indonesian people were felt very high if infected by Covid-19 due to no proper medicines or vaccine available yet for fighting the covid-19 disease. Based on analysis of collected data from information-sources interviews and literature studies it shows that among problems of work load and stress work having the most negative impact on personnel performance conducting decontamination task is there a combination of work load, coming in the form of a high number patients treated in Wisma Atlet RSDC, and stress work caused by individual personal problems, mainly such as receiving bad news that his family are positive being infected by Covid-19 and must be treated or quarantined at hospital, or must be isolated at home or have passed away caused by covid-19 disease. Those findings need serious and thorough attentions from the commander and leaders of Kizi Nubika Pusziad, especially if the organization receives order from Indonesian Army Headquarter to perform similar task at a reference emergency hospital as supporting efforts for responding to a non-natural disaster caused by the spread of new emerging disease which is much more contagious and complex than Covid-19 disease in the future.